(untitled) (The South East European Journal of Economics and Business, 2022)
The goal of this paper is to determine if there is product market integration in the euro area (EA). The paper employs LM and RALS-LM unit root tests with two breaks on the relative price series, constructed using the seasonally adjusted monthly Harmonized Index of Consumer Prices (HICP), from 1996:01 to 2017:05. The analysis shows EA-accession related breaks in price series for most of the EA11 countries, but, apart from Malta, no such breaks for the later-EA-joiners. However, there are breaks in both EA and non-EA countries at the time of EA formation. There is also evidence of greater product market integration and less adverse effects after negative shocks in the EA12. However, unit root analysis points to a conclusion that EA membership is not a sufficient condition for product market integration and integration is not necessarily related to being an EA member.